Detection of virus-neutralising antibodies and associated factors against rabies in the vaccinated household dogs of Kathmandu Valley, Nepal - Shikha Rimal (2020)
© 2020 Rimal et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. Background: Rabies is a vaccine-preventable neglected tropical viral zoonosis. It occurs worldwide, creating a very heavy burden in many developing countries, including Nepal. Dogs are the principle vector for the transmission of this disease in urban areas. Vaccination is the most important preventive measure in areas where dogs are the principle source of infection. This study was conducted with the aim of detecting virus-neutralising antibodies and associated factors against rabies in vaccinated household dogs of Kathmandu valley. Methods: Blood samples were collected from 110 vaccinated pet dogs in Kathmandu, Bhaktapur, and Lalitpur districts of Nepal. The samples were taken to the laboratory of the National Zoonosis and Food Hygiene Research Center where serum was separated. An indirect immune-enzymatic assay (PlateliaTM Rabies II kit ad usum Veterinarium, Biorad, China) was used for the detection of rabies virus anti-glycoprotein antibodies in the dog serum samples following the manufacturer's recommendations and instructions. Optical density values for unknown samples were compared with the positive sera titers in quantification tests obtained after a direct reading on the standard curve. Results were expressed as equivalent units per ml (EU/ml). Findings: Of the total samples, 89.09% exceeded the required seroconversion level (≥ 0.5 EU/ml); another 9.09% did not reach the seroconversion level (0.125-0.5 EU/ml); and 1.81% had undetectable seroconversion levels (<0.125 EU/ml) suggesting that the animal had not seroconverted according to the PLATELIA™ RABIES II test. Only one factor, the condition under which the dog was kept, was significantly associated with the antibody titer level. No association was found for any of the other factors included in the study. Interpretation Vaccination is the most effective measure for prevention and control of rabies. The locally manufactured brand of vaccine, which is available in Nepal, is potent enough to generate a sufficient amount of protective antibodies, equal to international brands.